John Randolph of Roanoke - Johnson, David E., 1961- (Book collections on Project MUSE., 2012)
One of the most eccentric and accomplished politicians in all of American history, John Randolph (1773-1833) led a life marked by controversy. The long-serving Virginia congressman and architect of Southern conservatism grabbed headlines with his prescient comments, public brawls, and clashes with every president from John Adams to Andrew Jackson. The first biography of Randolph in nearly a century, John Randolph of Roanoke provides a full account of the powerful Virginia planter's hard-charging life and his impact on the formation of conservative politics.